2002
DOI: 10.1037/0893-3200.16.3.243
|View full text |Cite
|
Sign up to set email alerts
|

A cognitive approach to child abuse prevention.

Abstract: This investigation tested the incremental utility of cognitive retraining as a component within a program designed to prevent child maltreatment. High-risk families (N = 96) were randomly assigned to a control condition, home visitation modeled after the Healthy Start program (unenhanced home visitation), or home visitation that included a cognitive component (enhanced home visitation). Mothers were identified late during pregnancy or soon after birth, and their participation continued for 1 year. Lower levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
215
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 227 publications
(224 citation statements)
references
References 58 publications
7
215
1
1
Order By: Relevance
“…In addition, prior research of parental transmission has shown that the manner in which a mother expresses her emotions is related to her child's emotion regulation (Eisenberg et al, 2001). Family influences, then, may include skills that parents learn regarding emotion regulation and parenting that will then affect their children, a family transmission that intervention studies have illustrated (Bugental et al, 2002).…”
Section: Stressor Severity: Genetic and Environmental Variancementioning
confidence: 99%
“…In addition, prior research of parental transmission has shown that the manner in which a mother expresses her emotions is related to her child's emotion regulation (Eisenberg et al, 2001). Family influences, then, may include skills that parents learn regarding emotion regulation and parenting that will then affect their children, a family transmission that intervention studies have illustrated (Bugental et al, 2002).…”
Section: Stressor Severity: Genetic and Environmental Variancementioning
confidence: 99%
“…Finally, Bugental et al (2002) reported an intervention targeted toward mothers who were at risk of making hostile attributions about their infants and engaging in physical abuse. Their cognitive intervention, focused on helping women understand that infants are not capable of behaving with hostile intent.…”
Section: Interventions To Alter Attributional Stylementioning
confidence: 99%
“…A Chi-square analysis (corrected for small samples) testing these differences revealed a trend-level difference (X 2 = 3.56, p =.07). Families also participated in an ongoing home visitation program in which they had been randomly assigned to either a cognitive reframing condition, or a condition focused on parent training and social support (employing methods described in Bugental, Ellerson, Lin, Rainey, Kokotovic, & O'Hara, 2002). A Chi-square analysis testing these differences revealed a trend-level difference among those who completed the program (X 2 = 3.30, p =.08).…”
mentioning
confidence: 99%